HYDROGEN LINES IN B-e STARS ENVELOPES - Udovichenko, S. N.; Konchagina, E. I. (Одеські астрономічні публікації, 2017)
The investigation of Balmer Hα and Hb line profiles for 28 Be and Be-shell stars have been carried out. The emission profiles of stars were obtained by subtracting from “A Be star atlas” photospheric line profiles which were computed from Kurucz models and corrected from gravity and rotation. The relationships between emission-line widths, equivalent widths and rotational velocity for 28 B-e stars confirm the origin of envelope these stars from rotational mass loss, consistent with a rotating, equatorial disk. The smaller emission disks shown the weak Hα emission lines. The biggest - the strong one.